"I Thought She Was Ordinary, I Only Saw Her Body": Sex and Celebrity Advocacy in Nigerian Popular Culture. Issue 4 (2nd October 2021) - Oyinlola Popoola, Rosemary
ABSTRACT: The twenty-first century ushered in a new era in African popular culture. Hip hop, a popular genre of musical expression, which borrowed extensively from Western and African idioms and iconography of power and social relations, took a decisive turn. The themes and narratives of twenty-first century African hip hop mirror similar global forms in their conception and glorification of fandom, stardom, commodification and sexualization of women's bodies, violence, and superfluous display of wealth. In this article, I examine some of the rare instances in which Nigerian male hip hop artists have used their talent and poetic license to call attention of the public to the economic and socio-political disenfranchisement of women. This article goes beyond a content analysis of the songs to underscore how core transformations in Nigeria's democratic process since 1999, when civil rule was reintroduced, have shaped the circumstances under which hip hop artists rethink their sexualization and commodification of women's bodies.